The Relationship between Self-efficacy and Compliance with Self-care Behaviors in Patients with Acute Coronary Syndrome after Coronary Angioplasty in Shahid Madani Hospital, 2016: A Health Belief Model - Mahdiyeh Alizadeh (Journal of Research in Medical and Dental Science, 2018)
Cardiovascular diseases are today one of the main causes of mortality and morbidity in many countries, seen in more than 19% of the country’s population. Therefore, this study was designed to determine the relationship between self-efficacy and compliance with self-care behaviors in cardiovascular patients using Health Belief Model (HBM). In this descriptive correlational study, 400 patients hospitalized in Ayatollah Shahid Madani Hospital of Tabriz were examined by simple sampling method. Data were collected using a questionnaire based on the HBM. Data were analyzed by descriptive and analytical tests using SPSS-19 software. The participant’s mean age was 63 years, 65% were male, 84.5% were married and most of them (61.5%) were illiterate or had elementary education; 43% of them had unstable acute coronary syndrome (ACS). There was a correlation between self-care behaviors and compliance with self-care behaviors (p<0.05). Multiple linear regressions showed that self-efficacy was a suitable variable for preventive behaviors in cardiovascular disease. According to the results, there is a correlation between self-care behaviors and self-efficacy. In other words, by increasing selfefficacy, self-care behaviors can be increased in patients that can prevent their re-admission.